THE CANADIAN LIVING TREE DOCTRINE OF CONSTITUTIONAL INTERPRETATION: A RECONCILEMENT BETWEEN THE PAST AND THE PRESENT IN CONSTITUTIONAL INTERPRETATION - Diniz Araujo, Luiz henrique (2020)
This paper aims to tackle the issue of constraints to constitutional interpretation in light of the Living Tree metaphor from the Canadian Constitutional Law. It further scrutinizes this doctrine in contrast to the Originalism and the Living Constitution doctrines developed in the United States. As a conclusion, the article acknowledges that the Living Tree metaphor has the merit for proposing a reconciliation between fixidity and flexibility in interpretation of the constitution. Nevertheless, in order to convey more objectivity and constraints to interpretation, it should be associated with consideration to precedents and incrementalism.